Preliminary Virtual Screening Studies to Identify GRP78 Inhibitors Which May Interfere with SARS-CoV-2 Infection - Palmeira, Andreia; Sousa, Emilia; Koseler, Aylin; Sabirli, Ramazan; Goren, Tarik; Turkcuer, Ibrahim; Kurt, Ozgur; Pinto, Madalena M.; Helena Vasconcelos, M. (MDPI, 2020)
SARS-CoV-2 Spike protein was predicted by molecular docking to bind the host cell surface GRP78, which was suggested as a putative good molecular target to inhibit Covid-19. We aimed to confirm that GRP78 gene expression was increased in blood of SARS-CoV-2 (+) versus SARS-CoV-2 (-) pneumonia patients. In addition, we aimed to identify drugs that could be repurposed to inhibit GRP78, thus with potential anti-SARS-CoV-2 activity. Gene expression studies were performed in 10 SARS-CoV-2 (-) and 24 SARS-CoV-2 (+) pneumonia patients. A structure-based virtual screen was performed with 10,761 small molecules retrieved from DrugBank, using the GRP78 nucleotide binding domain and substrate binding domain as molecular targets. Results indicated that GRP78 mRNA levels were approximately four times higher in the blood of SARS-CoV-2 (+) versus SARS-CoV-2 (-) pneumonia patients, further suggesting that GRP78 might be a good molecular target to treat Covid-19. In addition, a total of 409 compounds were identified with potential as GRP78 inhibitors. In conclusion, we found preliminary evidence that further proposes GRP78 as a possible molecular target to treat Covid-19 and that many clinically approved drugs bind GRP78 as an off-target effect. We suggest that further work should be urgently carried out to confirm if GRP78 is indeed a good molecular target and if some of those drugs have potential to be repurposed for SARS-CoV-2 antiviral activity.
Keywords: Covid-19; SARS-CoV-2; GRP78; gene expression; virtual screening; antiviral; repurposed drugs